The value of haptic feedback in conventional and robot-assisted minimal invasive surgery and virtual reality training: a current review - van der Meijden, O. A. J.; Schijven, M. P. (Surgical endoscopy, 2009)
Background Virtual reality (VR) as surgical training tool has become a state-of-the-art technique in training and teaching skills for minimally invasive surgery (MIS). Although intuitively appealing, the true benefits of haptic (VR training) platforms are unknown. Many questions about haptic feedback in the different areas of surgical skills (training) need to be answered before adding costly haptic feedback in VR simulation for MIS training. This study was designed to review the current status and value of haptic feedback in conventional and robot-assisted MIS and training by using virtual reality simulation. Methods A systematic review of the literature was undertaken using PubMed and MEDLINE. The following search terms were used: Haptic feedback OR Haptics OR Force feedback AND/OR Minimal Invasive Surgery AND / OR Minimal Access Surgery AND/OR Robotics AND/OR Robotic Surgery AND/OR Endoscopic Surgery AND/OR Virtual Reality AND/OR Simulation OR Surgical Training/Education. Results The results were assessed according to level of evidence as reflected by the Oxford Centre of Evidence-based Medicine Levels of Evidence. Conclusions In the current literature, no firm consensus exists on the importance of haptic feedback in performing minimally invasive surgery. Although the majority of the results show positive assessment of the benefits of force feedback, results are ambivalent and not unanimous on the subject. Benefits are least disputed when related to surgery using robotics, because there is no haptic feedback in currently used robotics. The addition of haptics is believed to reduce surgical errors resulting from a lack of it, especially in knot tying. Little research has been performed in the area of robot-assisted endoscopic surgical training, but results seem promising. Concerning VR training, results indicate that haptic feedback is important during the early phase of psychomotor skill acquisition.